SISTEM KEAMANAN RUANGAN MENGGUNAKAN SENSOR PIR DENGAN BUZZER ALARM DAN EMAIL NOTIFIKASI PADA SMAN 15 KOTA BEKASI - Yushi Sulistari; Fata Nidaul Khasanah (Institut Bisnis Muhammadiyah Bekasi, 2022)
Security systems using motion sensors provide the benefit of knowing crimes that occur using the prototype method, PIR sensors (Passive Infrared Receiver) as sensors to detect human motion so that, when human movement is detected by the PIR sensor, it will sound an alarm and send message notifications via e-mail users use e-mail, so users can find out about actions quickly. The research was carried out by installing motion detection sensors with buzzer alarms and email notifications in the principal, teacher, and administration rooms.